Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Using two or more complete sentences, describe and correct the error in the solution.

Solve the system of equations.

3x - 2y = 2

9x - 6y = 6

3x - 2y = 2 → 9x - 2y = 6
9x - 6y = 6 → 9x - 6y = 6
-8y = 12
y = 1.5
3x - 2y = 2 → 3x - 2(1.5) = 6
3x - 3 = 6
3x = 9
x = 3


Sagot :

Answer:

Step-by-step explanation:

3x - 2y = 2. (1)

9x - 6y = 6. (2)

Multiply equation (1) by 3 and (2) b 1

3x - 2y = 2 → 9x - 2y = 6 (3)

9x - 6y = 6 → 9x - 6y = 6 (4)

The error is equation (3)

It should be 9x - 6y = 6

-8y = 12

y = 1.5

3x - 2y = 2 → 3x - 2(1.5) = 6

3x - 3 = 6

3x = 9

x = 3

3x - 2y = 2

9x - 6y = 6

3x - 2y = 2 → 9x - 6y = 6. (3)

9x - 6y = 6 → 9x - 6y = 6. (4)

9x - 6y = 6 (3)

9x - 6y = 6 (4)